Why teach an NCLEX prep class?. Issue 2 (February 2015) - Parsh, Bridget; Sanders, Susan; Lilyquist, Karen
<x xml:space="preserve">Abstract</x> Because by doing so, you'll get a taste for teaching in a supportive environment—and maybe pump up your bottom line too. Better yet, you'll have the satisfaction of helping to prepare the next generation of nurses. This article explores how to get into this field.